WS2-induced enhanced optical absorption and efficiency in graphene/silicon heterojunction photovoltaic cells. Issue 43 (24th October 2018) - Debbarma, Rousan; Behura, Sanjay K.; Wen, Yu; Che, Songwei; Berry, Vikas
Abstract : By leveraging the Van Hove singularity induced enhancement in optical absorption, a photovoltaic cell is designed with WS2 on graphene atop n-Si to enhance the power conversion efficiency. Abstract : Van Hove singularity (VHS) induced enhancement of visible-frequency absorption in atomically-thin two-dimensional (2D) crystals provides an opportunity for improved light management in photovoltaics; however, it requires the 2D nanomaterial to be in close vicinity of a photojunction. In this report, we design a Schottky junction-based photovoltaic system with single-layer graphene atop n-type silicon (n-Si), which is interfaced directly with a few layers of tungsten disulfide (WS2 ) via a bottom-up CVD synthesis strategy. An enhanced power conversion efficiency in the architecture of WS2 -graphene/n-Si is observed compared to graphene/n-Si. Here, the WS2 induced photon absorption, with only three atoms above the photo-junction, enhanced the short-circuit current density ( J sc ), and the reconfiguration of the energy band structure led to effective built-in electric field induced charge carrier transport (enhanced open-circuit voltage ( V oc )). Similar to a graphene/n-Si Schottky junction, the WS2 -graphene/n-Si double junction exhibited non-linear current density–voltage ( J – V ) characteristics with a 4-fold increase in J sc (2.28 mA cm −2 in comparison with 0.52 mA cm −2 for graphene/n-Si) and 40% increase in the V oc (184 mV compared to 130 mV for graphene/n-Si) with a 6-fold increase in the photovoltaic power conversion efficiency. Futuristically, we envision an evolution in 2D heterojunctions with sharp transitions in properties within a few nanometers enabling control on optical absorption, carrier distribution, and band structure for applications including tandem photovoltaic cells and 2D optoelectronic circuit-switches.